Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1002/path.1018
|View full text |Cite
|
Sign up to set email alerts
|

Mature dendritic cells make clusters with T cells in the invasive margin of colorectal carcinoma

Abstract: Dendritic cells (DCs) take up tumour-specific antigen and migrate to regional lymph nodes to generate anti-tumour immunity. Although DC infiltration within human tumour tissue has been reported, the subset distribution has not been fully investigated. This study used immunohistochemistry to investigate DC subset distribution in colorectal adenocarcinoma. DCs expressing CD83, which are considered to be mature DCs, were present mainly in the invasive margin of cancer stroma. CD83(+) DCs in the invasive margin fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
73
2
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 22 publications
10
73
2
4
Order By: Relevance
“…Possibly, expression of DC-SIGN specifically on immature DCs enables these cells but not mature DCs to associate with colorectal tumors. The presence of immature DCs with proliferating CD4 and CD8 T cells has been reported (27,29). The numbers of these mature DCs and tumor-infiltrating lymphocytes correlate with a metastasis-free condition and the survival of colorectal cancer patients (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possibly, expression of DC-SIGN specifically on immature DCs enables these cells but not mature DCs to associate with colorectal tumors. The presence of immature DCs with proliferating CD4 and CD8 T cells has been reported (27,29). The numbers of these mature DCs and tumor-infiltrating lymphocytes correlate with a metastasis-free condition and the survival of colorectal cancer patients (30).…”
Section: Discussionmentioning
confidence: 99%
“…6). Previously, it was reported that immature DCs are present intratumorally, whereas mature DCs are located peritumorally (27,28). Possibly, expression of DC-SIGN specifically on immature DCs enables these cells but not mature DCs to associate with colorectal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is accumulating which suggests that the presence of dendritic cells may be of significant benefit to patients with colorectal cancer [82] . Using immunohistochemistry for CD83, Suzuki et al [83] described the presence of mature dendritic cells at the invasive margin of cancer stroma and demonstrated by light and electron microscopy their formation into clusters with lymphocytes, the majority of which were CD45RO+ T cells. They conclude that mature CD83+ dendritic cells at the invasive margin promote T-cell activation for the generation of tumor specific immunity.…”
Section: Macrophages Mast Cells Neutrophils and Dendritic Cellsmentioning
confidence: 99%
“…The location of the TIDC infiltrate mattered for the prognosis. Bell et al in breast cancer and Suzuki et al in colorectal carcinoma showed that mature DCs make clusters with T lymphocytes in the margin of tumors, whereas immature DCs invade the epithelium (Bell et al, 1999;Suzuki et al, 2002). In contrast, the opposite pattern was associated with a dismal prognosis in colorectal tumors (Sandel et al, 2005).…”
Section: Subsets Of DC With Specialized Functions?mentioning
confidence: 99%